How cognitive flexibility affects sense of power in a coffee virtual setting: The moderating role of personality traits - Loureiro, S. M. C.; Guerreiro, J.; Villar, J. (Extended reality and metaverse: Immersive technology in times of crisis, Conference proceedings, 2023)
In this study, we cross two sensory experiences, one with the senses of sight and sound and the other with the senses of sight, sound, and smell. The experience takes place in a Virtual Coffee and measures the impact it has on the sense of power. We analyse the concepts of Sense of Power and Cognitive Flexibility. Personality traits is analysed as a moderator in the relation between Sense of Power and Cognitive Flexibility. A sample of 125 individuals participated in the experiment. Results show that Cognitive Flexibility significantly and positively explains Sense of Power. Personality Traits moderates the relationship between Cognitive Flexibility and Sense of Power.